Multimorbidity is associated with fragility fractures in women 50 years and older - Barcelos, Anabela (2021)
Funding Information: The study was supported by unrestricted grants from Direcção-Geral da Saúde , Fundação Calouste Gulbenkian , Fundação Champalimaud , Fundação AstraZeneca , Abbvie , Merck, Sharp & Dohme , Pfizer , Roche , Servier , Bial , D3A Medical Systems , Happybrands , Center de Medicina Laboratorial Germano de Sousa , Clínica Médica da Praia da Vitória , CAL-Clínica , Galp Energia , Açoreana Seguros , and individual rheumatologists .